Understanding stress / Azman Taher - Taher, Azman (Universiti Teknologi MARA Cawangan Pahang, 1989)
Stress is a very common term among us. At a quick glance, being under stress is quite synonymous with being under pressure. But, is it? Have we ever felt like there is so much to do in very little time? Have we ever felt burned out? Have we ever experienced physical, mental and emotional fatigue? If we have, then these situations are normal in a working environment. Sometimes there is nothing left in us to make the extra effort. However, sometimes we have no problem in finding the extra "uumph" to go the mile. Basically, these are the situations and conditions stress can do to us. Stress can be constructive and, at the same time, can be destructive. Stress is closely related to one's profession. Physicians, surgeons, office managers and air traffic controllers usually face a great deal of stress whereas farmers, craft workers, and college professors face relatively low levels of stress. In later parts of this paper we will discuss how stress can be handled individually and organisationally. The main objective of this paper is to bring us closer towards the understanding of stress. The fact is, stress is a part of life that cannot be denied. Whether we like it or not, we constantly undergo stress. The only difference is the degree of severity of stress. The level of stress will vary from time to time. Therefore, the understanding of stress will assist us in managing and coping with stress more effectively. Hence, enhancing the level of performance and productivity.